Using social network tools to facilitate cultural adjustment of self-initiated Malaysian female expatriate nurses in Saudi Arabia - Bibi N. Mohd Yusuf; Norhayati Zakaria; Asmat-Nizam (Elsevier, 2021)
Background: This research study aims to:(1) identify and explore the social network communication tools used to facilitate the adjustment process of Malaysian female expatriate nurses working in the Kingdom of Saudi Arabia (hereafter "the Kingdom" or "SA") who are accompanied by neither their spouses nor families and (2) determine how these tools facilitate their adjustment to their new environment. Emphasis is placed on this particular group of respondents primarily due to the dearth of research conducted on female expatriate nurses. Method: We conducted a preliminary study using semi-structured interviews with sixteen (16) Malaysian female expatriate nurses working in SA to obtain a broader understanding of their experiences with cross-cultural adaptation and their use of social media tools to connect with their families and friends in their home country. Results: This study uncovers numerous social media communication tools being used by female expatriate nurses to help curb their loneliness and lessen the culture shock of living and working in a foreign country. Continuous engagement with these tools helps Malaysian female expatriate nurses maintain their emotional stability, thereby enabling them to remain mentally strong and ultimately prolonging their stay in SA. Conclusions: This study's outcomes contribute significantly to the knowledge of the government, various organizations, and aspiring female expatriate nurses in the healthcare industry because the results can assist female expatriate nurses during the adjustment period, enabling them to work efficiently and successfully in the host country.